Heterozygous mthfr c677t polymorphism (rs1801133) is associated with higher total cholesterol/ high density lipoprotein cholesterol ratio in habitual coffee drinkers - Ong, Xuan (2023)
Coffee consumption and its effect on cardiometabolic health have been studied for decades. Yet, the epigenetic effects of coffee on blood pressure, pulse and lipid profile have not been extensively known. Increased prevalence of cardiometabolic disease and mortality is now an emerging issue globally. While MTHFR C667T is widely known as a risk factor for cardiometabolic diseases, the impact of coffee and this polymorphism on cardiometabolic risk is unknown. Convenient sampling was applied and a total of 298 (110 males and 188 females) and 106 (37 males and 69 females) participants at UTAR Kampar were recruited for the cross-sectional and experimental study. Questionnaire were distributed. Genotype identification, blood pressure, pulse and lipid profile measurement were performed in the experimental study. SPSS Version 27.0 was used to analyze the data. The prevalence of coffee consumption was 34.9% in the study cohort. Significantly, male habitual coffee drinkers are higher than female (χ2=19.671, p < 0.001). Genotype distribution were 49.1%, 50% and 0.94% for CC, CT, and TT genotype. Interestingly, MTHFR C677T polymorphism was associated with habitual coffee consumption (χ2=8.0381, p < 0.05). Significant iii difference in the ratio of TC to HDL-C were found between habitual and non habitual coffee drinkers among the T allele carriers (p < 0.05). Among regular coffee drinkers, SBP (p < 0.05) and DBP (p < 0.05) increased significantly while pulse rate (p < 0.05) decreased after coffee consumption. Regular coffee intake increased cardiovascular risk particularly in heterozygous MTHFR C677T by increasing the ratio of TC to HDL-C. Acutely, the intake of coffee increased the SBP and DBP but decreased pulse rate of habitual coffee drinkers. In conclusion, epigenetics modifications can potentially mediate the effects of coffee on gene expression and physiological process. Future studies should consider gender differences, dietary factors, physical activity and larger sample size